PENGARUH MOTIVASI KERJA DAN SELF EFFICACY TERHADAP KINERJA KARYAWAN PADA PT. PELINDO (PERSERO) CABANG SIBOLGA - Tanjung, Vebri Yanti; Simatupang, Sahat; Simamora, Fauziah Nur (Jurnal Riset Manajemen dan Akuntansi, 2023)
This study aims to determine whether or not there is an influence of Work Motivation and Self Efficacy on Employee Performance at PT. Pelindo (Persero) Sibolga Branch. The hypothesis put forward is that there is an influence of work motivation and self-efficacy on employee performance at PT. Pelindo (Persero) Sibolga Branch. The author uses 46 respondents as a sample taken from 46 populations using the Sugiyono formula. The results of the study indicate that there is a positive relationship between work motivation and self-efficacy on employee performance at PT. Pelindo (Persero) Sibolga Branch and its correlation coefficient is 0.419, so when interpreted on a value scale it can be categorized as moderate. While the coefficient of determination is known that Work Motivation and Self Efficacy only contribute 33.3% to Employee Performance at PT. Pelindo (Persero) Sibolga Branch and the remaining 66.7% is influenced by other factors not examined. Regression equation obtained Y = 15.032 + 0.22X1 + 0.45X2 which shows that if you add one unit of variables X1 and X2 (Work Motivation and Self Efficacy) or a certain value, the variable Y (Employee Performance) will increase by the regression coefficient of 0.22 and 0. 45. Based on the results of hypothesis testing conducted by Employee Performance by comparing the t-count value of Work Motivation and t-table, it is found that the t-count value is smaller than t-table, namely 1.748 <2.016, Self- Efficacy and t-table, it is found that the t-count value is greater than t-table, namely 3.188 <2.016 and a significance value of 0.000 below α 5%. Because t count is greater than t table, there is an influence of Work Motivation and Self Efficacy on Employee Performance at PT. Pelindo (Persero) Sibolga Branch and the hypothesis proposed is accepted.